Computer-aided drug design, synthesis and identification of disulfide compounds as novel and potential allosteric PAK1 inhibitors. Issue 22 (27th March 2018) - Huang, Hanwei; Jiang, Hailun; Zhang, Xiangyu; Li, Wei; Wang, Pengliang; Liu, Funan; Wang, Jian; Bai, Mingfeng; Cheng, Maosheng
Abstract : p21-activated kinase 1 (PAK1) is an evolutionarily conserved serine/threonine protein kinase, which has been considered as one of the key regulatory factors in signaling network of tumor cells. Abstract : p21-activated kinase 1 (PAK1) is an evolutionarily conserved serine/threonine protein kinase, which has been considered as one of the key regulatory factors in signaling network of tumor cells. Therefore, inhibition of PAK1 may be a potential approach to treat many types of solid tumors. Several allosteric inhibitors of PAK1 have been identified, and the most well known one is IPA-3. But its biological activity is not satisfied, and the structure activity relationship (SAR) of PAK1 allosteric inhibitors is unclear. In this study, we designed and synthesized 13 potential allosteric inhibitors by using computer-aided drug design based on the structure of the existing PAK1 allosteric inhibitors. All the compounds were characterized by 1 H-NMR and 13 C-NMR, among which six were not reported previously. SAR was investigated by pharmacological studies and In03 and In06 showed increased PAK1 inhibition than previously reported IPA-3. These findings could guide further structure optimization of PAK1 inhibitors.